ELECTROMAGNETIC COUPLING IN FREQUENCY-DOMAIN INDUCED POLARIZATION DATA: A METHOD FOR REMOVAL - Routh P.S.; Oldenburg D.W. (My University, 2001)
Electromagnetic (EM) coupling is generally considered to be noise in induced polarization (IP) data and interpretation is difficult when its contribution is large compared to the IP signal. The effect is exacerbated by conductive environments and large-array survey geometries designed to explore deeper targets. In this paper we present a methodology to remove EM coupling from frequency-domain IP data. We first investigate the effect of EM coupling on the IP data and derive the necessary equations to represent the IP effect for both amplitude and phase responses of the signal. The separation of the inductive response from the total response in the low-frequency regime is derived using the electric field due to a horizontal electric dipole and it is assumed that at low frequencies the interaction of EM effects and IP effects is negligible. The total electric field is then expressed as a product of a scalar function, which is due to IP effects, and an electric field, which depends on the EM coupling response. It is this representation that enables us to obtain the IP response from EM-coupling-contaminated data. To compute the EM coupling response we recognize that conductivity information is necessary. We illustrate this with a synthetic example. The removal method developed in this work for the phase and the per cent frequency effect (PFE) data are applicable to 1-D, 2-D and 3-D structures. The practical utility of the method is illustrated on a 2-D field example that is typical of mineral exploration problems.
Keywords: ELECTROMAGNETIC COUPLING; INDUCED POLARIZATION; INVERSION; MINERAL EXPLORATION; NOISE